2018
DOI: 10.1111/bld.12212
|View full text |Cite
|
Sign up to set email alerts
|

“I carry her in my heart”: An exploration of the experience of bereavement for people with learning disability

Abstract: Accessible summary Four people with learning disability talked about what it was like when someone they cared about had died. They said that it was important they were included, but that it was hard. They said they carried on loving the person after they died and that they missed them. Abstract BackgroundBereavement is a universal experience, yet little research has explored the lived experience of bereavement for people with learning disability (PWLD). Materials and methodsFour PWLD were interviewed about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Seventeen of the included studies (68%) reported levels of intellectual disabilities (see Table 1). Nine studies (53%) (Cithambaram et al, 2019, 2020; Cithambarm et al, 2021; Forrester‐Jones, 2013; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; Thorp et al, 2018; Tuffrey‐Wijne et al, 2013) collected data from people with mild to moderate disabilities and all used interviews. Five studies (29%) (Chow et al, 2017; Rodríguez Herrero et al, 2015; Tuffrey‐Wijne et al, 2009; Tuffrey‐Wijne, Bernal, & Hollins, 2010; Tuffrey‐Wijne, Bernal, Hubert, et al, 2010) collected data from people with mild, moderate, and severe intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen of the included studies (68%) reported levels of intellectual disabilities (see Table 1). Nine studies (53%) (Cithambaram et al, 2019, 2020; Cithambarm et al, 2021; Forrester‐Jones, 2013; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; Thorp et al, 2018; Tuffrey‐Wijne et al, 2013) collected data from people with mild to moderate disabilities and all used interviews. Five studies (29%) (Chow et al, 2017; Rodríguez Herrero et al, 2015; Tuffrey‐Wijne et al, 2009; Tuffrey‐Wijne, Bernal, & Hollins, 2010; Tuffrey‐Wijne, Bernal, Hubert, et al, 2010) collected data from people with mild, moderate, and severe intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Where reported (10/17, 59%), duration of the interviews ranged from 15 to 90 min (Cithambaram et al, 2020; Cithambarm et al, 2021; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; McKenzie et al, 2017; Rodríguez Herrero et al, 2015; Ryan et al, 2012; Thorp et al, 2018; Voss et al, 2020). Only two studies reported interviews taking place over multiple days (Haider & Zaman, 2022; McRitchie et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The stories of self‐advocates often began with the sharing of difficult life experiences. Such life experiences are common for people with intellectual disabilities, who can be disabled by times of loneliness (Petroutsou et al, 2018), loss of meaningful relationships (Thorp et al, 2018), experiences of bullying (Olivier et al, 2020), abuse (Buhagiar & Azzopardi Lane, 2020), poor employment opportunities (Khayatzadeh‐Mahani et al, 2020), ill health (Anderson et al, 2013) and mental illness (Perera et al, 2020). The stories of self‐advocates were very much unified by a common theme of overcoming adversity and finding ways of being heard.…”
Section: Discussionmentioning
confidence: 99%
“…Thorp et al (2018) explored bereavement experiences of people with a learning disability, noting difficulties expressing emotions, and experiences of missing the deceased. Thorp et al (2018) concluded that emotions associated with grief are likely to be as overwhelming for people with a learning disability as in the general population, yet complicated by limitations in communicating and expressing emotional states. Given the barriers to how, when, and why people with learning disabilities might experience grief, there is a risk that they experience disenfranchised grief (Doka, 1999), where the grief expression is not in line with societal norms around death and grieving.…”
Section: Introduction 1| Bereavement In Learning Disabilitiesmentioning
confidence: 99%